Pengembangan Bahan Ajar Kimia Interaktif Berbasis Proyek dan Etnosains untuk Meningkatkan Kemampuan Berpikir Kreatif Mahasiswa pada Pengajaran Laju Reaksi - Eva Pratiwi Pane; Ady Frenly Simanullang; Ivan Samuel; Sunggul Pasaribu; Bernard Simanjuntak; Dian Arisetya (UNIB Press, 2026)
Project-based learning is a learning strategy where students must build their own content knowledge and demonstrate new understanding gained through various forms of representation. Learning containing ethnoscience based on local wisdom, invites students to be close to their surrounding environment and be able to understand the phenomena that occur around them so that they can create a generation of products that are responsive and sensitive to the social and cultural environment of the nation. Chemistry learning can be integrated into ethnoscience because it involves contextual experiences in everyday life about local wisdom as learning materials and phenomena that exist in society. This study aims to develop interactive teaching materials based on projects and ethnoscience on the material of reaction rates that can improve students' creative thinking skills. This study uses the type of Research and Development (R&D) development research, with the ADDIE model. Data collection techniques are observation techniques, written tests, questionnaires and documentation. The results of the study obtained: (1) The proportion of students' creative thinking skills completion in the experimental class and control class is more than 75%; (2) The average creative thinking skills of students using interactive teaching materials based on projects and ethnoscience on the material of reaction rates is greater than the completion value.; (3) Analysis of two-way tests proves that the application of interactive project-based and ethnoscience-based teaching materials on reaction rate material has an effect on students' creative thinking skills; (4) Analysis of the N-Gain test of the experimental class and control class shows a moderate increase, namely 0.4 and 0.3.